Metodologia para análise da dependência térmica da germinação pelo modelo de grausdia - Cardoso, Victor José Mendes [UNESP] (Oecologia Australis, 2011)
The effects of temperature on the rate of biological processes such as the germination are reported in several papers. The analysis of the thermal effect can be performed either from numerical indices or germination curves, which is usually presented as the accumulated percentage of germination versus time. Such curves can be fitted by empirical models and generally they offer a better description of the time-course of germination than single-value indices. On the other hand, in analyzing the germination curves, a question arises whether the model parameters have biological meaning. Thus, it is desirable that the model parameters both describe properly the germination curve and have biological meaning, which often does not occur. Considering the involvement of populations and percentages in germination assays, an analytical model has been widely used in the last two decades which is based on the concept of thermal time. This article discusses the conceptual basis and provides procedures for applying the thermal-time model in germination studies by using the probit regression method, both at infra and supra-optimal temperatures.
Methodology for analysis of the thermal dependence of germination by thermal-time model
Keywords: Modeling; Review; Seeds; Temperature; Thermal time